2020
DOI: 10.3390/plants9060784
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Metabolism and Nitrogen Reshuffling Are Regulated by Reversible Cysteine Thiol Oxidation Following Nitrogen Deprivation in Chlamydomonas

Abstract: As global temperatures climb to historic highs, the far-reaching effects of climate change have impacted agricultural nutrient availability. This has extended to low latitude oceans, where a deficit in both nitrogen and phosphorus stores has led to dramatic decreases in carbon sequestration in oceanic phytoplankton. Although Chlamydomonas reinhardtii, a freshwater model green alga, has shown drastic systems-level alterations following nitrogen deprivation, the mechanisms through which these alterations are tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 93 publications
(145 reference statements)
1
5
0
Order By: Relevance
“…The functional annotation chart of target genes for the nitrogen deficiency-responsive miRNAs revealed some factors involved in the regulation of lipids biosynthesis (acyl-CoA synthetase, fatty acid desaturase), lipid transport (long-chain acyl-CoA transporter), and fatty acid beta-oxidation (Pristanoyl-CoA/acyl-CoA oxidase), were all predicted, indicating that various aspects in the lipid metabolic process may be regulated by some nitrogen deficiency-responsive miRNAs in C. reinhardtii . A recent study found that under nitrogen stress, C. reinhardtii lipids synthesize related proteins: acetyl CoA synthetase, two fatty acid desaturases, and a phospholipase-B-like protein change rapidly, indicating a trend of transformation from metabolism to TAG synthesis at the post-transcriptional level [ 52 ], which is consistent with this study. Similarly, LIP4, a putative TAG lipase in C. reinhardtii, is transcriptionally upregulated in the presence of nitrogen deficiency and TAG accumulation [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…The functional annotation chart of target genes for the nitrogen deficiency-responsive miRNAs revealed some factors involved in the regulation of lipids biosynthesis (acyl-CoA synthetase, fatty acid desaturase), lipid transport (long-chain acyl-CoA transporter), and fatty acid beta-oxidation (Pristanoyl-CoA/acyl-CoA oxidase), were all predicted, indicating that various aspects in the lipid metabolic process may be regulated by some nitrogen deficiency-responsive miRNAs in C. reinhardtii . A recent study found that under nitrogen stress, C. reinhardtii lipids synthesize related proteins: acetyl CoA synthetase, two fatty acid desaturases, and a phospholipase-B-like protein change rapidly, indicating a trend of transformation from metabolism to TAG synthesis at the post-transcriptional level [ 52 ], which is consistent with this study. Similarly, LIP4, a putative TAG lipase in C. reinhardtii, is transcriptionally upregulated in the presence of nitrogen deficiency and TAG accumulation [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…Chlorophyll synthesis and catabolism were dynamically balanced, and the change in the ratio of Chls a/b under different physiological conditions was reflected in this experiment’s transcriptome data. After 12 h of high light treatment, the expressions of glutamate-1-semialdehyde 2,1-aminomutase-related genes ( Table 1 ) were up-regulated to promote the production of Chl b [ 47 , 48 ]. The expression level of pheophorbide hydrolase-related genes, which was the key rate-limiting enzyme of the chlorophyll catabolism pathway, was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Protein‐level enrichment of reversible cysteine oxidation was performed as described previously (McConnell et al ., 2018; Smythers et al ., 2020). To show that alkylation of reduced cysteines was complete and to reduce false positive changes in reversible oxidation, a negative enrichment control was generated by pooling 15 μg from every sample (480 μg total) and then mock‐reduced with water.…”
Section: Methodsmentioning
confidence: 99%